Peningkatan Mutu Jerami Padi, Dedak Padi dan Onggok dengan Fermentasi Fungi dan Yeast - S.N.O. Suwandyastuti; Efka Aris Rimbawanto; Prayitno Prayitno (Jurnal Agripet, 2012)
The quality improvement of rice straw, rice bran and cassava waste by fermentation of fungi and yeast ABSTRACT. Biomass of agricultural residues are highly potential as ruminant feedstuff. However, it is characterized by high content of indigestible fiber and low nutritive value, due to the strong hydrogen bonds in the lignocelluloses. Biological treatment by using microbes seems to be an alternative, because of the capability, with no pollution problem. An experiment has been conducted to seek for the fungi and yeast which capable to improve the quality of rice straw, rice bran and cassava waste. The trial was done by the technique of in sacco and in vitro, in a completely randomized block design. The variables measure were : dry matter and protein digestibility, protein solubility and nutrient composition of the fermentation product. Based on the all variables measure, the current study concluded that the microbes chosen were : monoculture of T. viride for rice straw, monoculture of A. niger for rice bran and biculture of A luchuensis and S. cereviseae for cassava waste.